PREPOSISI BAHASA INGGRIS DAN BAHASA TALAUD DALAM KITAB YESAYA (SUATU ANALISIS KONTRASTIF) - WANDO, PAULINA REGA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â This research entitled â€œPreposition in English and Talaud Language in the Book of Isaiah (A Contrastive Analysis)â€. This research design aims at contrasting Preposition in English and Talaud language in the book of Isaiah in their forms and meanings in the sentence structure. Â Â The problems of this research are what are the forms and meanings of preposition in English and Talaud language in the book of Isaiah and to find out the similarities and differences between them. The purpose of this study is to identify, classify, the forms and meanings of preposition in English and Talaud language in the book of Isaiah and to analyze the differences and similarities of preposition in these two languages. Â The method of this study is descriptive method. Theories that used are Chrystal (1999), Aarts and Aarts (1982), Harman (1992) and Lado (1972). Investigation has been done through the library and field research. The English data has been collected from the Bible written in English, linguistic books, and from internet and whereas the Talaud data has been collected from the Bible written in Talaud language and the native informant speakers. Â Â The result shows that English and Talaud language have similarities and differences in forms and meanings. In terms of form there is one-word preposition and multi-word preposition in English whereas in the Talaud language this case just found one preposition based on the data obtained. In terms of meaning both English and Talaud language have similarities. Â Theoretically, the significance of this study is to give a reference in terms of prepositions especially the similarities and differences between English and Talaud language and is expected to be useful to develop syntax. Practically, this research is expected to help the students of English department or other readers in learning about preposition, especially about the forms and meanings of both language. Â Â Keywords: Preposition, English and Talaud language, Contrastive Analysis